2022
DOI: 10.1007/s00170-022-09295-w
|View full text |Cite
|
Sign up to set email alerts
|

A generic asset model for implementing product digital twins in smart remanufacturing

Abstract: A digital twin is a “live” virtual replica of a sensorised component, product, process, human, or system. It accurately copies the entity being modelled by capturing information in real time, or near real time, from the entity, through embedded sensors and the Internet-of-Things. Many applications of digital twins in the manufacturing industry have been investigated. This article focuses on, and contributes to, the development of product digital twins to reduce the impact of quantity, quality, and demand uncer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 95 publications
0
9
0
Order By: Relevance
“…Using the list of uncertainties by Rizova et al 12 , namely, (1) demand for remanufactured products, (2) returns quality, (3) returns quantity, (4) lead time, (5) returns timing and (6) routing, it has already been shown that product DTs, which are digital models with details of how the product was used throughout its service life, can offer information on 2, 3, 4 and 5. On the other hand, a process DT, which models the remanufacturing operation, is likely to yield data enabling remanufacturers to handle 6 11 . In combining the two DTs to create an end-to-end DT, all uncertainties could be contested to some degree.…”
Section: Literature Reviewmentioning
confidence: 99%
See 4 more Smart Citations
“…Using the list of uncertainties by Rizova et al 12 , namely, (1) demand for remanufactured products, (2) returns quality, (3) returns quantity, (4) lead time, (5) returns timing and (6) routing, it has already been shown that product DTs, which are digital models with details of how the product was used throughout its service life, can offer information on 2, 3, 4 and 5. On the other hand, a process DT, which models the remanufacturing operation, is likely to yield data enabling remanufacturers to handle 6 11 . In combining the two DTs to create an end-to-end DT, all uncertainties could be contested to some degree.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This research explores the inner workings of the decision-making module (DMM) identified in 11 and depicted in Fig. 1 as a key element of a remanufacturing-centric DT.…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations